The Power of Innovation, Distribution and Supervision Factor in Improving Performance of Supply Chain Management of Subsidized Fertilizer in Indonesia - Aswin Naldi Sahim; Nik Kamariah Nik Mat; Enjang Sudarman (International Journal of Supply Chain Management, 2018)
Supply chain (SC) is increasingly recognized as an important factor for improving business performance. Because of that, the SC activities need to be optimized and this can be done through the supply chain management (SCM). This study has three key objectives: to reveal the influence of government policy in terms of supervision, to check the reliability of distribution and innovation factors on the execution of the SCM of subsidized fertilizer in Indonesia. A sum of 800 questionnaire have been spread to the test site and a number of 587 or 73% successfully returned. Furthermore, the data from 513 respondents, or 64% of the spread, was analyzed by statistical software Structural Equation Modeling (SEM). The findings from this study shows that the government policy in terms of supervision and the reliability of the appropriation has immediate and critical impact on execution SCM of subsidized fertilizer. However although there is no immediate impact on the execution of SCM, factor of innovation plays a significant role because it determines the success of supervision and reliability of the distribution. Moreover, this supervision factor and the reliability of the distribution act as a mediator between the factors of innovation with the full performance of SCM. To improve the performance of SCM of subsidized fertilizer in Indonesia, this research suggests that the government pays attention to supervision, the reliability of the distribution as well as innovation factors. Due to that, the distribution of fertilizer will be more suited to its purpose at the right time with the appropriate location, type, quantity and the right quality, and at an appropriate price. In future research, the same study could be utilized for other subsidized commodities.